PENGARUH PEMBELAJARAN BERBASIS TEKS TERHADAP KEMAMPUAN MENULIS TEKS DESKRIPTIF - Desti Arjuni; Dwi Nursapitri; Nurlisa Nurlisa (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
Students’ ability to write descriptive texts still faces various challenges, including developing ideas, selecting appropriate vocabulary, and organizing texts coherently. This condition indicates that writing instruction has not fully provided students with an adequate understanding of the characteristics of descriptive texts. This study aims to examine the effect of text-based learning on students’ descriptive writing skills. The research employs a qualitative approach using a library research method by analyzing textbooks, scholarly journals, and relevant research articles published.The data were analyzed using content analysis techniques. The findings reveal that text-based learning effectively enhances students’ understanding of text structure, linguistic features, and their ability to compose descriptive texts clearly and coherently. Therefore, text-based learning can serve as an effective alternative approach to improving students’ writing skills.